2016
DOI: 10.1111/1471-0307.12368
|View full text |Cite
|
Sign up to set email alerts
|

Flowability and wetting behaviour of milk protein ingredients as influenced by powder composition, particle size and microstructure

Abstract: This work aimed to provide a comprehensive characterisation of several physicochemical properties of different milk protein powders frequently used as ingredients in dairy-based food formulations, in particular flowability and wettability. The flow and wetting properties were influenced mainly by the powder composition, less than by other physicochemical properties, such as particle size and microstructure. Powders with high fat content had poor flow and wetting properties. The wetting properties were also inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 43 publications
3
30
0
Order By: Relevance
“…In other words, the distribution of fine particles in the samples influenced dispersibility results and dissolution performance. These dispersibility results and their related dissolution performance are in accordance with the existing evidence from the published literature such as Ji et al (2016) and Silva and O'Mahony (2016). Similarly, the bulk density result of the samples varies from 0.42 to 0.60 g/cm 3 , shown in Table 2 Figure 2 Raw near-infrared spectra of milk powder samples with different particle size distribution and quality attributes.…”
Section: Particle Size Distribution Dispersibility and Bulk Density supporting
confidence: 87%
See 1 more Smart Citation
“…In other words, the distribution of fine particles in the samples influenced dispersibility results and dissolution performance. These dispersibility results and their related dissolution performance are in accordance with the existing evidence from the published literature such as Ji et al (2016) and Silva and O'Mahony (2016). Similarly, the bulk density result of the samples varies from 0.42 to 0.60 g/cm 3 , shown in Table 2 Figure 2 Raw near-infrared spectra of milk powder samples with different particle size distribution and quality attributes.…”
Section: Particle Size Distribution Dispersibility and Bulk Density supporting
confidence: 87%
“…These dispersibility results and their related dissolution performance are in accordance with the existing evidence from the published literature such as Ji et al . (2016) and Silva and O'Mahony (2016). Similarly, the bulk density result of the samples varies from 0.42 to 0.60 g/cm 3 , shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The particle size distribution of the FMWC was measured by laser diffraction, using a Malvern Mastersizer 3000 (Malvern Instruments Ltd., Malvern, United Kingdom) with an automated dry powder Aero S dry dispersion unit, as described by Silva and O’Mahony [ 33 ]. The air pressure and powder feed rate were 1.5 bar and 30%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…(2017) studied the physical properties of whole and skimmed milk powders (WMP and SMP), and reported that these properties were influenced by the method of drying, processing conditions, and ingredients. Silva and O’Mahony (2016) investigated the flowability and wettability of several milk protein powders, and found that these properties were affected by fat and protein contents. Similarly, the flow properties of milk powder of different fat contents (Szulc et al., 2012), infant milk powders (Crowley et al., 2014), spray‐dried milk powders (Fitzpatrick et al., 2005), and milk protein concentrates (Teunou et al., 1999) have been reported.…”
Section: Introductionmentioning
confidence: 99%